EFL Teachers’ Interpretation of Curriculum: The Cases of an Elementary Schools - Marsevani, Maya; Putra, Rizki; Zaki, Leil Badrah (Lingual Journal of Language and Culture, 2024)
The teaching of English subject in elementary schools with the 2013 Curriculum is quite common. Many teachers have different perspectives on the curriculum whether it’s the strategies or challenges in the implementation of the teaching process. This study goal is to view the perspective of English teacher interpretation of 2013 Curriculum. This research uses observation checklists and interviews. This study involves 3 English teachers that teach elementary school to be observed and interviewed. Researchers conducted an observation on one of the teachers while they teach and conducted interview face to face with the 3 teachers. The data that was gathered was then sorted out in the observation checklists and transcription. The results showed that teachers have various teaching methods that they use, such as implementing interactive lessons, engaging in group discussion, encouraging students in activity and collaboration, providing opportunities to students, and the use of technology. Meanwhile, challenges in teaching occur such as limitation of teaching resources, large class size, and time limitations. It could be concluded that while teachers implement teaching methods in 2013 Curriculum teaching, it could still raise some problems for them. The implication of this study is that teachers are supposed to adapt to the curriculum to provide a great learning environment.